The Integration of Sanad in the Contextual Interpretation of the Qur'an: A Maqasid-Based Perspective: (Integrasi Sanad dalam Penafsiran Kontekstual Al-Qur’an: Sebuah Perspektif Berbasis Maqasid) - Akib, Moh. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
While contextual approaches frequently lack this epistemic anchor, which raises questions about legitimacy, classical Islamic scholarship emphasizes sanad (chain of transmission) as the primary criterion for authenticating Qur'anic interpretations based on Prophetic traditions. By combining sanad-based validation with maqasid al-shari‘ah (higher objectives of Islamic law), this study offers a compromise that results in interpretations that are both legitimate and pertinent. The framework involves two steps: first, isnad-based validation using isnad and matn criticism to verify textual authenticity (riwayah sahihah); second, maqasid-driven interpretation using the values of public welfare, justice, and mercy to bring meaning into line with modern contexts. By ensuring authenticity comes before contextualization, this